2011
DOI: 10.1002/tox.20673
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of food contaminant furan on liver and kidney of growing male rats

Abstract: Furan is a chemical used in some industrial products and occurs naturally in heat-treated foods. We aimed to investigate the effects of orally administered furan on liver and kidney in growing Wistar male rats for 90 days. In this respect, biochemical, morphological, histopathological, and histomorphometrical examinations were performed. Three- to 4-week aged rats were divided into five groups of eight animals each; control, oil control; 2, 4, 8 mg/kg/day furan treatment groups. At the end of the experiment, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…In our work in diabetic furan treated rats, there were significantly decreased activities in SOD, CAT, GST, and GPx compared with diabetic control rats. Similar to our work, Selmanoglu, Karacaoğlu, Kılıç, Koçkaya, and Akay () and Ucar and Pandır () have also shown that antioxidants’ activities were shown to change in rats fed on furan. The alterations in activities of enzymes can be due to the generation of ROS (Baş, Kalender, Pandır, & Kalender, ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our work in diabetic furan treated rats, there were significantly decreased activities in SOD, CAT, GST, and GPx compared with diabetic control rats. Similar to our work, Selmanoglu, Karacaoğlu, Kılıç, Koçkaya, and Akay () and Ucar and Pandır () have also shown that antioxidants’ activities were shown to change in rats fed on furan. The alterations in activities of enzymes can be due to the generation of ROS (Baş, Kalender, Pandır, & Kalender, ).…”
Section: Discussionsupporting
confidence: 89%
“…Furan causes undesirable effects in living things (Gill et al, ). Another study showed that furan influenced the antioxidant defense system (Selmanoglu et al, ). In this study, MDA, which is the indicator of LPO, was measured and the damage was determined.…”
Section: Discussionmentioning
confidence: 99%
“…Incremental MDA was determined in the liver of furan-exposed rats. Selmanoğlu et al (34) also reported enhanced MDA levels in furan toxicity in their work.…”
Section: Discussionmentioning
confidence: 85%
“…Alterations of antioxidant enzyme activities observed in this work may be due to the production of ROS. Selmanoğlu et al (34) reported that treatment of rats with furan showed changes in antioxidant enzyme activities. Connections between chemical treatment and alterations in antioxidant enzyme activities have been proven (36).…”
Section: Figure 6 (A) Liver Section Of Control Rats Cv: Central Veinmentioning
confidence: 99%
“…Furthermore, the authors observed an increased mitotic activity in the subcapsular regions of the left and caudate lobe accompanied by an occasional apoptotic cell and inflammatory foci with accumulation of mononuclear cells. Selmanoglu et al (2012) treated juvenile male Wistar rats by gavage with 2, 4 or 8 mg/kg bw per day over 90 days. A 7 days per week dose schedule was applied (Karacao glu, 2016, E-mail communication, 25 October 2016).…”
Section: A Furanmentioning
confidence: 99%